Role of Protégé Personality in Receipt of Mentoring and Career Success - Turban, Daniel B.; Dougherty, Thomas W. (Academy of Management Journal, 1994)
We used structural equation modeling to investigate relationships among protégés' personality characteristics, initiation of mentoring, mentoring received, and career success for 147 managers and professionals. Protégés influenced the amounts of mentoring they received by initiating relationships with mentors. Internal locus of control, high self-monitoring, and high emotional stability enhanced initiation, which mediated the relationships between personality characteristics and mentoring received. The latter was related to career attainment and perceived career success, and career attainment influenced perceived success. Finally, protégé gender was not related to initiation or mentoring received.